Parotid pilomatrixoma: Diagnostic trap and management dilemma - Bhardwaj, Abhishek; Angral, Sumeet; Chandra, Sharath; Malhotra, Manu; Priya, Madhu; Varshney, Saurabh; Singh, Arpana; Raj, Ritu (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Pilomatrixoma is a benign cutaneous adnexal neoplasm originating from the matrix cells of the hair follicles. Usually a slow growing and painless lesion, it must be considered in differential diagnosis of a preauricular swelling. Rapidly progressive lesion with skin fixity and missed subtle cytological features may lead to a misdiagnosis of parotid neoplasm resulting in management dilemma. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. This report emphasizes consideration of pilomatrixoma as a differential diagnosis in a similar clinical scenario, the role of frozen section during surgery and fascia lata interposition to prevent Frey’s syndrome. A brief review of literature is presented. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. We present a similar dilemmatic case of a 19 years old male with preauricular swelling. Based on cytology and image findings, a diagnosis of parotid neoplasm with possible malignancy was made. Surgical exploration revealed primarily a subcutaneous lesion with partial attachment to superficial surface of parotid. Lesion was excised with a cuff of normal parotid tissue. Frozen section confirmed it to be a nonmalignant lesion with possibility of pilomatrixoma. Fascia lata was interposed between parotid and thin skin flap to avoid gustatory sweating. Patient is on follow up for 6 months without recurrence or any complication. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Pilomatrixomas can be misdiagnosed in case of lesions in subcutaneous plane in parotid region. In such cases, the differential diagnosis should include tumor and non-tumor lesions of skin and parotid gland. Importance of frozen section should also be kept in mind and the pathologist should be engaged at the time of surgical excision of the tumor. Interposition of soft tissue between parotid and thin skin flap helps prevent gustatory sweating in such cases. A high index of suspicion is needed for proper diagnosis and management of these lesions.